Legal Smuggling in Land Ownership Nominee Agreement by Foreigners In Indonesia - amalia, riza; Sunaryo, Sunaryo; Kasmawati, Kasmawati; Ria, Ria Wierma Putri (Jurnal Hukum Malahayati, 2024)
In a nominee agreement on land ownership by foreigners in Indonesia, the objective requirement is a cause what is halal is not fulfilled, it will result in the agreement becomes null and void by law. It means from the beginning of an agreement and/or an agreement thought to have never been born/never existed. Article 1335 of the Civil Code states that a an agreement made under false pretenses or forbidden has no power. In this case, the agreement was deemed to have been void from the beginning because not all agreements made have binding force as law.